PENGARUH KEBISINGAN LALU LINTAS TERHADAP TINGKAT KETERGANGGUAN INDIVIDU SISWA (Studi Kasus : SMPN 3 Kendari)) - Sabta Nur Ibnu (Jurnal Manajemen Rekayasa (Journal of Engineering Management), 2019)
Noise are unwanted sounds from activities in certain level and certain time can cause health problem and environmental problem. Noise is an annoying thing in studying process, in long time intensity and certain level can be dangerous for health. Therefore, the education zone need a quiet environmet from noise including traffic noise.The goal of this research are to analyze the noise level from traffic activities in SMPN 3 Kendari, to analyze students perception about traffic noise in SMP Negeri 3 Kendari and to analyze the influence of noise level to student’s level of annoyance in SMPN 3 Kendari. The results of this research showed that the noise level from traffic activity in SMPN 3 Kendari has exceeded the standard noise limit for education zone with average Leq value are 77,5 dB. Students perception to traffic noise level are : not disturbed 30%, quite disturbed 41%, moderately disturbed 19%, disturbed 8%, and very disturbed 2%.The noise level has a significant influence to students annoyance level with regression model: Y = 2·10-11 X6.1553 and R2 value = 0.5837 with noise level as independent variable (X) and annoyance level as dependent variable (Y).Keywords: Noise, Annoyance, School